Effectiveness of acupuncture for the recovery of gastrointestinal function of patients with gastric cancer in the postoperative period: A protocol for systematic review and meta-analysis. Issue 7 (19th February 2021) - Li, Huaiyu; Chen, Yun; Hu, Ziyi; Jiang, Jiawang; Li, Renliang; Qiu, Qianjie; Ye, Jing
Abstract: Background: Gastric cancer (GC) is the most common malignant tumors in the world and surgical resection remains the primary treatment for it. Postoperative patients often suffer from gastrointestinal dysfunction as the most common side effects of surgery for GC patients. Acupuncture has a regulatory effect on gastrointestinal function. We conducted this study to assess the effectiveness of acupuncture on the restoration of gastrointestinal function of postoperative patients with GC. Methods: Seven electronic databases will be searched from inception to November 2020 to identify any relevant study: Medline, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), China National Knowledge Infrastructure (CNKI), Wanfang Database, Chinese Biomedical Literature Database (CBM), and Chinese Scientific Journal Database (VIP database). No restriction on time and language. The primary outcome measure will be the Time to First Flatus and secondary outcome measures include the time of first defecation and the quality of life (QOL) and the number of patients with abdominal distention. We will use EndNote V.9.1 to screen the eligible literature and the I 2 statistic to assess heterogeneity in the included studies. The meta-analysis will be conducted using the Review Manager (RevMan) software (V.5.3). Results: Our study aims to systematically assess whether the pooled effects of currently available trials prove effects of acupuncture in improving gastrointestinal function of patients with GC in the postoperative period. Conclusion: This study will conduct an evaluation about the efficacy of acupuncture for the recovery of gastrointestinal function of patients with GC in the postoperative period, making up for the lack of relevant clinical evidence. INPLASY registration number: INPLASY2020110066.